Answer:
Explanation:
Area = length * width
length: x + 3
width: x - 5
A = (x + 3)(x - 5)
Simplify (x + 3)(x - 5) using the FOIL method:
1. First numbers: multiply the first number of each binomial together--x*x = x%5E2
2. Outer numbers: multiply the outer number of each binomial (out of the entire expression, the number farthest to the left (x) and the number farthest to the right (-5))--x*-5 = -5x
3. Inner numbers: multiply the inner number of each binomial--3*x = 3x
4. Last numbers: multiply the last number of each binomial--3*-5 = -15
==> Now, add all of the results together and combine like terms: x%5E2+-+5x+%2B+3x+-+15 = x%5E2+-+2x+-+15
Therefore, A = x%5E2+-+2x+-+15